English graphic novels in the teaching of literature in a school in Jitra, Kedah / Aimi Syafiqah Ghazali - Ghazali, Aimi Syafiqah (Faculty of Education, 2014)
This study aims to determine the effects of the usage of graphic novels in the teaching of literature in school in Jitra, Kedah. The usage of the graphic novel in the syllabus is still new and needs to be monitored and studied in order to find out the impact it gives towards the learning of Literature in schools. There is a total of 67 respondents from Sekolah Menengah Sultan Abdul Halim, Jitra, Kedah, which were involved in this study. Sixty four of them are the students while the remaining three respondents are the teachers from the same school. The questionnaires were distributed in order to collect the data and interviews with the teachers were conducted there as well. The study reveals the lists of effects that are gained from the teaching of the graphic novel, and also the perception of the teachers towards the material as well. Based on the findings found by the researcher, several implications and recommendations are included in this study for the reference of future researches.